The Yin and Yang of Alarmins in Regulation of Acute Kidney Injury - Sabapathy, Vikram; Venkatadri, Rajkumar; Dogan, Murat; Sharma, Rahul (Frontiers in Medicine, 2020)
Acute kidney injury (AKI) is a major clinical burden affecting 20-50% of hospitalized and intensive care patients. Irrespective of the initiating factors, the immune system plays a major role in amplifying the disease pathogenesis with certain immune cells contributing to renal damage, whereas others offer protection and facilitate recovery. Alarmins are small molecules and proteins that include granulysins, high-mobility group box 1 protein (HMGB1), interleukin (IL)-1α, IL-16, IL-33, heat-shock proteins (HSP), the Ca++ binding S100 proteins, ATP and Uric acid. Alarmins are mostly intracellular molecules and their release to the extracellular milieu signals cellular stress or damage, generally leading to the recruitment of the cells of the immune system. Early studies indicated a proinflammatory role for the alarmins by contributing to immune-system dysregulation and worsening of AKI. However, recent developments demonstrate anti-inflammatory mechanisms of certain alarmins or alarmin sensing receptors, which may participate in the prevention, resolution, and repair of AKI. This dual function of alarmins is intriguing and has confounded the role of alarmins in AKI. In this study, we review the contribution of various alarmins to the pathogenesis of AKI in experimental and clinical studies. We also analyze the approaches for the therapeutic utilization of alarmins for AKI.